2022
DOI: 10.3390/ani12131708
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Survey and Genetic Characterization of Anaplasma marginale in Ticks Collected from Livestock Hosts in Pakistan

Abstract: Ticks transmit pathogens to animals and humans more often than any other arthropod vector. The rural economy of Pakistan mainly depends on livestock farming, and tick infestations cause severe problems in this sector. The present study aimed to molecularly characterize the Anaplasma spp. in hard ticks collected from six districts of Khyber Pakhtunkhwa, Pakistan. Ticks were collected from various livestock hosts, including cattle breeds (Holstein-Friesian, Jersey, Sahiwal, and Achai), Asian water buffaloes, she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…In the phylogenetic tree based on bacterial 16S rRNA, the clade of A. marginale and A. ovis clustered as a sister clade to the clade of A. centrale. This relatedness is also represented by their ecological and epidemiological aspects because these three species commonly infect ruminants [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the phylogenetic tree based on bacterial 16S rRNA, the clade of A. marginale and A. ovis clustered as a sister clade to the clade of A. centrale. This relatedness is also represented by their ecological and epidemiological aspects because these three species commonly infect ruminants [24].…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that this field of research has attracted attention, there are still very few available studies restricted to a few areas in Pakistan about the molecular data of ticks and Anaplasma spp. [2,8,13,18,[22][23][24]. Our previous study has demonstrated the molecular assessment of hard ticks and associated A. marginale collected from livestock hosts in the northern and central regions of Khyber Pakhtunkhwa (KP), Pakistan [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…infection. This method is widely applied for the detection of pathogens [ 33 ]; it is very sensitive at first [ 7 ] but quickly loses sensitivity following appropriate antibiotic administration. A negative result does not exclude the diagnosis, as intermittent levels of bacteremia could produce false-negative results.…”
Section: Discussionmentioning
confidence: 99%
“…Rhipicephalus and Hyalomma ticks are the most common tick species prevalent in cows and buffaloes in Pakistan (19)(20)(21). According to a recent study conducted in different zones of KP (Khyber Pakhtunkhwa), Pakistan, 3 major tick species, Rhipicephalus microplus, Rhipicephalus haemaphysaloides, and Rhipicephalus turanicus, showed positive results for Anaplasma marginale, the causative agent of anaplasmosis (22). In a recent paper, future concerns about ticks and tick-borne diseases were discussed (23).…”
Section: Introductionmentioning
confidence: 99%